2014
DOI: 10.5430/wje.v4n2p65
|View full text |Cite
|
Sign up to set email alerts
|

Spelling Development among Triangle versus Native Bedouin Arabic Pupils

Abstract: This study compared spelling development of consonants (guttural: /ḥ/, uvular-velar: /q/ and /ġ/, emphatic: /ḏḍ/, /ṯṭ/, and /ðҐ, and dental: /ṯ/) in the written form of Arabic among native Bedouin Arabic speakers from north and southern Israel (N=666), versus native Arabic pupils from the triangle (N=153), learning in second, fourth, and sixth grades. Three tasks were constructed for this study: real word dictation, pseudo-word dictation, and real word recognition. The results show significantly higher scores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…In addition, it was found that Bedouin pupils experienced difficulty representing emphatic phonemes in the written form of Arabic, and represented them by a similar phoneme, for example /s/ and /ṣ/, or /d/ and /ḍ/ (for detailed explanation of similar phonemes see : Fragman 2014). Previous studies have related to spelling errors in general and spelling errors of similar phonemes in Arabic in particular among native Arabic pupils explaining them as a result of the diglossic nature of Arabic (Saiegh-Haddad, 2003.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it was found that Bedouin pupils experienced difficulty representing emphatic phonemes in the written form of Arabic, and represented them by a similar phoneme, for example /s/ and /ṣ/, or /d/ and /ḍ/ (for detailed explanation of similar phonemes see : Fragman 2014). Previous studies have related to spelling errors in general and spelling errors of similar phonemes in Arabic in particular among native Arabic pupils explaining them as a result of the diglossic nature of Arabic (Saiegh-Haddad, 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Henkin (2010) have highlighted sociolinguistic aspects and stylistic variation of the Bedouin dialects of the Negev as well. However, only few studies conducted recently (Fragman 2013(Fragman , 2014 focused on aspects of language acquisition and specifically the spelling development of the written form of Arabic among Bedouin pupils in elementary schools from a linguistic point of view. This study seems of importance; Several studies focused on education in the Bedouin sector of the Negev (Abu Rabia A., 2001; Abu-Sa'ad, 1991, 1995, 1996 Al-Haj, 1995, 2003 Dinero, 2002;Elbedour, El-Bassiouny, Burt, and Elbedour 2013;Krä tli, 2000) showed poor achievements among the Bedouin pupils, for example in the "Meitzav" tests in Arabic and additional subjects (Rudnitzky, 2012).…”
Section: Introductionmentioning
confidence: 99%